The Dendritic Cell Synapse: A Life Dedicated to T Cell Activation - Benvenuti, Federica (Frontiers in Immunology, 2016)
T cell activation within immunological synapses is a complex process whereby different types of signals are transmitted from antigen presenting cells to T cells. The molecular strategies developed by T cells to interpret and integrate these signals have been systematically dissected in recent years and are now in large part understood. On the other side of the immune synapse dendritic cells (DCs) participate actively to synapse formation and maintenance by remodeling of membrane receptors and intracellular content. However the details of such changes have been only partially characterized. The DCs actin cytoskeleton has been one of the first systems to be identified as playing an important role in T cell priming and some of the underlying mechanisms have been elucidated. Similarly, the DCs microtubule cytoskeleton undergoes major spatial changes during synapse formation that favor polarization of the DCs subcellular space toward the interacting T cell. Recently we have begun to investigate the trafficking machinery that controls polarized delivery of endosomal vesicles at the DC-T immune synapse with the aim of understanding the functional relevance of polarized secretion of soluble factors during T cell priming. Here we will review the current knowledge of events occurring in DCs during synapse formation and discuss the open questions that still remains unanswered.